Новые палеоарктические виды комаров-лимониид (Diptera, Limoniidae). VI. Роды Dicranomyia Steph. и Rhipidia Mg. - Савченко, E.H. (Вестник зоологии, 1974)
Four new species and one new subspecies of Limoniid-flies from the subfamily Li- moniinae, tribe Limoniini are described and figured: Dicranomyia (s. str.) dichroa S a v. (Tajik SSR), Dicranomyia (s. str.) violovitschi Sa v. (Tuva Autonomous SSR), Rhipidia (s. str.) tessulata Sa v. (Kazakh SSR), R. (s. str.) lucea Sa v. (Azerbajan SSR) and R. (s. str.) uniseriata lutea Sav. (Kirghiz SSR). The typical specimens of D. dichroa are preserved in the Zoological Institute, Leningrad, all other typical specimens in the Institute of Zoology, Kiev.